A Novel Fabrication of Dose-Dependent Injectable Curcumin Biocomposite Hydrogel System Anesthetic Delivery Method for Care and Management of Musculoskeletal Pain - Xuehong Jiang; Shuaishuai Wang; Hui Chen (SAGE Publishing, 2020)
Chronic musculoskeletal pain has biological, psychological, and social components. In this article, we have demonstrated the easily injectable nanocomposite carrier for the treatment of chronic musculoskeletal pain. Briefly, the curcumin (Cur) loaded with lipid nanocapsules (LNCs; Cur@LNCs) using the phase invasion method. The synthesized Cur@LNCs were characterized by using scanning electron microscopy, transmittance electron microscopy, and the size of the fabricated nanoparticles confirmed by dynamic light scattering analysis. The synthesized Cur@LNC injectable hydrogel shows excellent results in vivo in the rat model. We have examined the efficiency of the chronic constriction injury in the rat model and induced the pain using thermal paw withdrawal latency. The injectable hydrogels Cur@LNCs display a remarkable reduction in pain 7 days post administrations compared to the untreated group animals. This work could establish the preclinical candidate of the neuropathic pain response in the future.